Effect of Si and Mn on Microstructure and Mechanical Properties of Vacuum Suction Casting Al–4.5Cu Alloy - He, T.; Liu, H.; Shi, X.; Huo, Y.; Li, M.; Pan, T. (Проблемы прочности, 2018)
The high performance of alloys is dependent on microstructure, while alloying elements have significant influence on microstructure. In order to study the effect of Si and Mn elements on the microstructure and mechanical properties, different content of alloying elements, Si and Mn, are added into the matrix Al–4.5Cu alloy. The compounded alloys (CA) are prepared by vacuum suction casting. The microstructure of CA is investigated by a scanning electron microscope (SEM). The mechanical properties are tested by a universal testing machine and a microhardness tester. Analysis is conducted by comparing experimental results of CA with different content of Si and Mn. Высокая эффективность сплавов зависит от микроструктуры, при этом легирующие элементы оказывают значительное влияние на микроструктуру. В матрицу сплава Al 4,5Cu добавляли различное количество легирующих элементов Si и Mn для изучения их влияния на микроструктуру и механические свойства. Комбинированные сплавы отливали методом вакуумного всасывания. Микроструктуру комбинированных сплавов исследовали с помощью растрового электронного микроскопа. Механические свойства определяли при испытании на универсальной машине и посредством тестера микротвердости. Проанализированы экспериментальные результаты для сплавов с различным содержанием Si и Mn. Висока ефективність сплавів залежить від мікроструктури, при цьому легуючі елементи значно впливають на мікроструктуру. У матрицю сплава Al 4,5 Cu додавали різну кількість легуючих елементів Si i Mn для вивчення їх впливу на мікроструктуру і механічні властивості. Комбіновані сплави відливали методом вакуумного всомктування. Мікроструктуру комбінованих сплавів досліджували за допомогою растрового електронного мікроскопа. Механічні властивості визначали при випробуваннях на універсальній машині та за допомогою тестера мікротвердості. Проаналізовано експериментальні результати для сплавів із різним вмістом Si i Mn.